Routine Histopathological Examination After Cholecystectomy - Siddiue, Md Abu Bakar; Mahmud, Firoz; Faisal, M Fardil Hossain; Rahman, Md Fazlur; Das, Bidhan C; Mahmud, Riaz (KYAMC Journal, 2020)
Background: Cholecystectomy is one of the commonest surgeries in medical practice. Sometimes malignant condition cannot be assessed pre-operatively. Histopathology require for tissue diagnosis. Objective: To assess whether the histopathogical examination is really needed for all bladder specimens resected for cholelithiasis and cholecystitis. Materials and Methods: This observational study was carried out in the General Surgery Unit, Department of Surgery, Bangabandhu Sheikh Mujib Medical University, Dhaka from May, 2016 to April, 2017. A total number of 95 patients were included in this study. Results: Total of 95 gallbladder specimens were submitted for histopathological examination where 33.7% were males and 66.3 % were females with mean age of 46+12.86 years. Chronic cholecystitis was the most common finding in 91.6% of cases whereas Xanthogranulomatous 2.1%. Six of the gall bladders showed adenocarcinoma (6.3%), of which four had changes on ultrasound and macroscopic gall bladder analysis (MGAS) disturbances were found in 5 cases and 1 case was found incidentally on histopathological examination. On ultrasound, only four (66.66%) and peroperative macroscopic examination by surgeon only 5(83.3%) had a clue of carcinoma. Conclusion: It could be concluded that , routine histopathological examination of gallbladder after cholecystectomy is necessary as USG sometimes can not differentiate neoplastic lesion from inflammatory one. KYAMC Journal Vol. 10, No.-4, January 2020, Page 184-187